EFFECTS OF FOREX TRADING ON ECONOMIC GROWTH OF NIGERIA (Journal of the Management Sciences, 2023)
This study investigated the effect of Forex Trading on Economic Growth of Nigeria (1995-2021) using secondary data from Statistical bulletin of Central Bank of Nigeria. The research work used vector autoregressive (VAR) techniques to test the effect between the independent variables (CBN's Supply of Forex, Exchange Rate, and Foreign Exchange Reserve) on the dependent variable (gross domestic product). The study found that forex trading has insignificant effect on Nigeria economic growth within the period of the study. As a result, the study recommends that the government encourage export-oriented industries, diversify the economy, and invest in infrastructure. Additionally, there is a need to improve forex market liquidity and strengthen forex reserve management. Similarly, there is a need to encourage remittances from abroad while also ensuring collaboration among the government, central bank, and other relevant stakeholders in developing and implementing coordinated policies that support forex trading and economic growth.
Keywords: Forex Trading; RGDP